元宝枫种仁营养成分分析Nutritional components of Acer truncatum seed kernel - 张凯，徐娟，韦承珊，付晓娜，刘祥义 ZHANG Kai，XU Juan，WEI Chengshan，FU Xiaona，LIU Xiangyi (Zhongguo youzhi, 2023)
为明确元宝枫种仁的营养成分，对元宝枫种仁含油率、粗蛋白质含量，元宝枫种仁粕中氨基酸组成及含量、矿质元素组成及元宝枫种仁油的总脂肪酸、Sn-2位脂肪酸组成及含量、生育酚含量进行测定。结果表明：元宝枫种仁的含油率为43.7%，粗蛋白质含量为35.13%；元宝枫种仁粕中含有17种氨基酸，其中7种人体必需氨基酸占氨基酸总量的33.78%，是理想的蛋白质资源；元宝枫种仁粕中含有丰富的矿质元素，常量元素中K含量为6 372.8 μg/g，Na含量仅为346.5 μg/g，属于高钾低钠食品，微量元素中Mn含量较高，为68.1 μg/g，且未检出重金属元素；元宝枫种仁油主要由12种脂肪酸组成，神经酸含量达到5.89%，以亚油酸和α-亚麻酸为主的多不饱和脂肪酸主要分布在Sn-2位；元宝枫种仁油中生育酚总量为1 230.70 mg/kg，以γ-生育酚含量最高，达到792.62 mg/kg。元宝枫种仁营养丰富，可作为神经酸、生育酚和氨基酸的重要来源，其油脂可作为富含神经酸的保健食用油。 To clarify the nutritional components of Acer truncatum seed kernel, the contents of oil and crude protein in Acer truncatum seed kernel, the amino acid composition and mineral element composition of Acer truncatum seed kernel meal, the composition of total fatty acids, Sn-2 fatty acids and tocopherol content in Acer truncatum seed kernel oil were analyzed. The results showed that the contents of oil and crude protein in Acer truncatum seed kernel were 43.7% and 35.13% respectively. Acer truncatum seed kernel meal contained 17 kinds of amino acids, of which 7 kinds of essential amino acids accounted for 33.78%, and it was an ideal protein resource. Acer truncatum seed kernel meal was rich in mineral elements, with K content in major elements of 6 372.8 μg/g, and Na content of 346.5 μg/g, belonging to high potassium and low sodium food. The Mn content in trace elements was higher(68.1 μg/g), and no heavy metal element was detected. Acer truncatum seed kernel oil was mainly composed of 12 kinds of fatty acids, and the content of nervonic acid reached 5.89%. Polyunsaturated fatty acids, mainly linoleic acid and α-linolenic acid, were mainly distributed in Sn-2 position. The total contents of tocopherols in Acer truncatum seed kernel oil was 1 230.70 mg/kg, in which γ- tocopherol content was the highest, reaching 792.62 mg/kg. Acer truncatum seed kernel is rich in nutrition and can be used as an important source of nervonic acid, tocopherol and amino acids. Acer truncatum seed kernel oil can be used as a health edible oil.